Investigation of Resonance Transition X-Ray Radiation of 300 - 900 MeV Electrons in Layered Targets at Tomsk Synchrotron; International symposium Radiation from Relativistic electrons in periodic structures RREPS-93, September 6-10, 1993, Tomsk, Russia - Andreyashkin M. Yu.; Kaplin V. V. Valeriy Viktorovich; Zabaev V. N. Viktor Nikolaevich; Uglov S. R. Sergey Romanovich (1993, 1993)
В фонде НТБ ТПУ отсутствует